Interpersonal contacts of Polish traveling clergyman in the 18th century - Rok, Bogdan (Saeculum Christianum. Pismo Historyczne, 2021)
The text presents different types of interpersonal contacts in the course of journeys, based on Polish clergymen’s travel reports from the 18th century. The clergy establish numerous contacts, primarily with other travellers of the clerical estate. Also, information about meetings with pilgrims and people on subsequent stages of the journey can be found. Interestingly, contacts include Poles and important people of that time. It is important to emphasize the assertiveness of clergy travellers and their openness towards representatives of foreign nations.